UV photocureable coating as well as preparation method and application thereof
By using self-initiating polyurethane acrylate in UV light curing coatings, the problems of heavy odor and obvious color changes in traditional coatings after curing are solved, and a low-odor and low-color distortion coating film is achieved, which is suitable for high standards in modern industry. need.
Patent Information
- Application Number
- CN202411487282.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-23
- Publication Date
- 2025-02-18
AI Technical Summary
After curing, the coating film has a heavy odor and obvious color changes, making it difficult to meet the high standard needs of modern industry for rapid curing and environmentally friendly performance.
Polyurethane acrylate with self-initiating characteristics is used as the main film-forming substance. By introducing photo-initiating structural units into its molecular structure, it can initiate the curing reaction under ultraviolet light irradiation, eliminating additional photoinitiators and reducing coating. Odor and color changes in the film.
It realizes the low odor and low color distortion characteristics of UV light curing coatings, and is suitable for application areas with high requirements for odor and color stability, such as children's furniture, cabinets and interiors of wardrobes and other confined spaces.
Smart Images

Figure BDA0005099242110000021 
Figure BDA0005099242110000022 
Figure BDA0005099242110000061
Abstract
Description
Technical Field
[0001] The present application relates to the field of coating technology, and in particular to a UV light-curing coating and a preparation method and application thereof. Background Art
[0002] UV light-curing coatings, also known as ultraviolet curing coatings or photosensitive coatings, are coatings that can quickly cure into films under ultraviolet (UV) irradiation. At present, UV light-curing coatings on the wood coating market are mainly divided into two categories: oil-based UV light-curing coatings and water-based UV light-curing coatings. In general, the main difference between the two lies in the difference in dispersion medium. The former uses organic solvents, while the latter uses water as a dispersion medium. Water-based UV light-curing coatings are a high-efficiency, green, energy-saving and high-quality light-curing material because of their low VOC content (VOC content refers to the content of volatile organic compounds (Volatile Organic Compounds) in products such as coatings). They have been widely used in many fields such as office furniture, cabinets and handicrafts. The film-forming mechanism of water-based UV light-curing coatings relies on the cross-linking polymerization reaction of carbon-carbon double bonds in the light-curing resin under the action of active free radicals generated by photoinitiators, thereby achieving curing and film formation. Based on this curing mechanism, photoinitiators become an indispensable component in the formula. However, traditional small molecule photoinitiators have defects such as yellowing, odor, high volatility and easy migration, which makes it difficult for them to meet the high standards of fast curing and environmental performance in modern industrial production. Specifically, the odor emitted by the coating after curing is usually caused by the residual initiator and its decomposition products with chromophore small molecules.
[0003] In view of the problems of film discoloration and odor in the formulation design of traditional UV light-curing coatings, it has become an urgent task to improve them. Summary of the invention
[0004] In view of the above problems, the present application provides a UV light-curing coating and a preparation method thereof, aiming to solve the problem that the UV light-curing coating has a strong odor and obvious color changes in the coating film after curing.
[0005] In a first aspect, an embodiment of the present application provides a UV light-curing coating, which includes the following components in weight percentage, based on the total weight of the UV light-curing coating being 100%:
[0006]
[0007] Wherein, the polyurethane acrylate contains a photoinitiator structural unit, and the structural formula of the photoinitiator structural unit is shown in Formula I or Formula II:
[0008]
[0009] Wherein, * indicates the connection site.
[0010] The embodiment of the present application uses polyurethane acrylate with self-initiating properties as the main film-forming material of UV light-curing coating, and no additional photoinitiator is added to the formula. By adding auxiliary components such as wetting and leveling agents, defoaming agents, thickeners, etc., a water-based UV light-curing coating with low odor and low discoloration characteristics after UV curing is prepared. The self-initiating properties of the polyurethane acrylate are derived from the photoinitiating structural units contained in its structure. Under the irradiation of ultraviolet light sources, these structural units can self-cleave to generate active free radicals, and then initiate the carbon-carbon double bond functional groups in the molecular chain segments to undergo free radical polymerization reactions, and finally form a coating film with a cross-linked network structure. This coating is suitable for application areas that have high requirements for odor and color stability, such as children's furniture, cabinets, and confined spaces such as the interior of wardrobes.
[0011] In some embodiments, the polyurethane acrylate satisfies at least one of the following (1) to (5):
[0012] (1) The acrylate functionality of the polyurethane acrylate is 6 to 8;
[0013] (2) Each molecule of the polyurethane acrylate contains 2 to 3 photoinitiator structural units;
[0014] (3) The solid content of the polyurethane acrylate is 35% to 45%;
[0015] (4) The viscosity of the polyurethane acrylate at 25° C. is 50 cP to 500 cP;
[0016] (5) The number average molecular weight of the polyurethane acrylate is 5000 g / mol to 20000 g / mol.
[0017] One or more polyurethane acrylates that meet the above conditions are suitable for the UV light-curing coating of the embodiments of the present application, which helps to form a more complex and stable network structure, thereby improving the mechanical properties and chemical stability of the coating film.
[0018] In some embodiments, the defoamer includes a polyether-modified polysiloxane copolymer and a foam-breaking siloxane solution. As such, since the two defoamers have complementary and synergistic effects in performance, when used in combination, the same defoaming effect can be obtained while reducing the dosage, thereby reducing production costs and reducing the impact on the environment.
[0019] In some embodiments, the polyether-modified polysiloxane copolymer includes BYK-028 and TEGO-902W; the defoaming siloxane solution includes BYK-024. Thus, when these three defoamers are used in combination, not only can the overall dispersion effect and defoaming and degassing speed be improved, but also production efficiency can be improved, and the quality of the coating can be further optimized.
[0020] In some embodiments, the mass ratio of the BYK-028 to the TEGO-902W and the BYK-024 is (15-25): (25-35): 50. In this way, the defoaming effect is better and the coating quality is higher.
[0021] In some embodiments, the wetting and leveling agent includes at least one of polyether-modified polydimethylsiloxane and acetylene glycol; and / or the thickener includes an associative polyurethane thickener. Thus, the above-mentioned types of wetting and leveling agents and thickeners are applied to the UV light-curing coatings of the embodiments of the present application to further improve the comprehensive performance of the coatings.
[0022] In some embodiments, the Stormer viscosity of the UV light-curing coating is 70KU to 90KU at 25° C. This indicates that the coating has good fluidity, which is conducive to uniform application during construction, simplifies the construction process and saves time, and helps to form a smooth and uniform coating film, thereby improving the appearance quality of the coating.
[0023] In a second aspect, an embodiment of the present application provides a method for preparing a UV light-curing coating, comprising the following steps: providing raw materials for the UV light-curing coating according to the first aspect; mixing polyurethane acrylate, a wetting and leveling agent, a defoaming agent, and a thickener to obtain a mixed slurry, and when the fineness of the solid particles in the mixed slurry is ≤30μm, adding water and a thickener to the mixed slurry, and adjusting the Stormer viscosity to 70KU~90KU at 25°C to obtain a UV light-curing coating.
[0024] The preparation method of the embodiment of the present application adds water and thickener to adjust the viscosity after the fineness reaches the standard of less than or equal to 30 μm, so that the slurry can be fully dispersed without affecting the quality. The UV light-curing coating prepared by this method has a smooth surface, high gloss and good visual effect.
[0025] In a third aspect, the embodiments of the present application provide an application of the UV light-curing coating according to the first aspect or the UV light-curing coating prepared by the preparation method of the second aspect in the field of environmentally friendly coatings.
[0026] In this coating formulation, traditional photoinitiators are not introduced, but the photoinitiator structural units in the polyurethane acrylate oligomer are directly used. Under ultraviolet (UV) irradiation, these photoinitiator structural units can efficiently generate active free radicals, which in turn trigger the UV-induced cross-linking curing process of the carbon-carbon double bonds in the oligomer. The cleverness of this design strategy is that the addition of photoinitiators is omitted, thus giving the final coating film the excellent characteristics of low odor and low discoloration, making it an ideal choice in the field of environmentally friendly coatings.
[0027] In a fourth aspect, the present application provides a method for using the UV light-curing coating as in the first aspect or the UV light-curing coating prepared by the preparation method of the second aspect, comprising the following steps: applying the UV light-curing coating on a substrate by spraying and / or roller coating; wherein the coating amount by spraying is 100 g / m 2 ~150g / m 2 The coating amount by roller coating is 5g / m 2 ~20g / m 2 ; Dry the coated substrate at a drying temperature of 40℃~60℃ for 1h~24h; then use UV light curing with a light curing energy of 300mJ / cm 2 ~1200mJ / cm 2 .
[0028] The above description is only an overview of the technical solution of the present application. In order to more clearly understand the technical means of the present application, it can be implemented in accordance with the contents of the specification. In order to make the above and other purposes, features and advantages of the present application more obvious and easy to understand, the specific implementation methods of the present application are listed below. DETAILED DESCRIPTION
[0029] In order to make the technical problems, technical solutions and beneficial effects to be solved by the present application more clearly understood, the present application is further described in detail below in conjunction with the embodiments. It should be understood that the specific embodiments described herein are only used to explain the present application and are not used to limit the present application.
[0030] In this application, the term "and / or" describes the association relationship of associated objects, indicating that there may be three relationships. For example, A and / or B can mean: A exists alone, A and B exist at the same time, and B exists alone. A and B can be singular or plural. The character " / " generally indicates that the associated objects are in an "or" relationship.
[0031] In this application, "at least one" means one or more, and "plurality" means two or more. "At least one of the following" or similar expressions refers to any combination of these items, including any combination of single items or plural items. For example, "at least one of a, b or c", or "at least one of a, b and c", can all mean: a, b, c, ab (i.e. a and b), ac, bc, or abc, where a, b, c can be single or multiple, respectively.
[0032] It should be understood that in the various embodiments of the present application, the size of the serial numbers of the above-mentioned processes does not mean the order of execution, some or all of the steps can be executed in parallel or sequentially, and the execution order of each process should be determined by its function and internal logic, and should not constitute any limitation on the implementation process of the embodiments of the present application.
[0033] The terms used in the embodiments of the present application are only for the purpose of describing specific embodiments, and are not intended to limit the present application. The singular forms "a", "said" and "the" used in the embodiments of the present application and the appended claims are also intended to include plural forms, unless the context clearly indicates other meanings.
[0034] The weight of the relevant components mentioned in the embodiment description of the present application can not only refer to the specific content of each component, but also represent the proportional relationship between the weights of the components. Therefore, as long as the content of the relevant components is proportionally enlarged or reduced according to the embodiment description of the present application, it is within the scope disclosed in the embodiment description of the present application. Specifically, the mass described in the embodiment description of the present application can be a mass unit known in the chemical industry such as μg, mg, g, kg, etc.
[0035] Water-based UV light-curing coatings are popular in industries such as office furniture, cabinets and handicrafts for their high efficiency, environmental protection and energy saving. The curing process of UV light-curing coatings relies on photoinitiators to activate double bonds in the resin, prompting chemical cross-linking reactions to form solid coatings. However, traditional small molecule photoinitiators have problems with yellowing, odor, volatility and migration, and do not meet the requirements of modern industry for fast and environmentally friendly processes. These initiators remain in the coating or decompose to produce colored small molecules, which are the main cause of the odor of the final product.
[0036] Based on this, the embodiment of the present application provides a UV light-curing coating, which includes the following components in weight percentage, based on the total weight of the UV light-curing coating as 100%: 65% to 85% of polyurethane acrylate; 0.1% to 1% of wetting and leveling agent; 0.1% to 1% of defoaming agent; 0.1% to 1% of thickener; 10% to 35% of water; wherein the polyurethane acrylate contains a photoinitiator structural unit, and the structural formula of the photoinitiator structural unit is shown in Formula I or Formula II:
[0037]
[0038] Wherein, * indicates the connection site.
[0039] The polyurethane acrylate in the embodiment of the present application is a type of polyurethane acrylate material that can generate active substances such as free radicals to initiate a curing reaction under UV light or other external stimuli without the need to add additional photoinitiators. The polyurethane acrylate in the embodiment of the present application has this self-initiating property because its molecular structure contains a specific photoinitiating structural unit.
[0040] The photoinitiator structural unit shown in Formula I contains active groups such as benzene rings and carbonyl groups. These groups can absorb light energy of a specific wavelength under UV light irradiation, causing electron transitions and bond breakage inside the molecule, thereby triggering photolysis reactions to generate active substances such as free radicals. These generated free radicals are highly reactive and can quickly trigger the acrylate group (i.e., the portion containing a carbon-carbon double bond) in the polyurethane acrylate to undergo a chain growth reaction.
[0041] The photoinitiator structural unit shown in Formula II contains a benzopyrone ring formed by a benzene ring and a pyrone ring connected by a conjugated double bond. In this structure, the π electrons of the benzene ring and the π electrons of the pyrone ring form an extended conjugated system. The pyrone ring contains not only a carbon-carbon double bond, but also a lactone structure. The two are connected to each other through conjugation, allowing the π electrons in the entire ring system to move freely. This conjugated system can absorb light of a specific wavelength. After absorbing light energy, the molecule enters an excited state, and then promotes the polymerization reaction of the carbon-carbon double bond through an energy transfer mechanism.
[0042] The UV light-curing coating provided in the embodiment of the present application is characterized by containing polyurethane acrylate with self-initiating properties. The material realizes self-initiating polymerization under UV light by introducing a photoinitiating structural unit into the polyurethane acrylate molecule. Therefore, no additional photoinitiator is required in the formula, thereby avoiding the problem of strong odor and obvious color change after curing caused by residual photoinitiator and its decomposition products.
[0043] The UV light-curing coating formula provided in the embodiment of the present application also includes three additives: a wetting and leveling agent, a defoamer, and a thickener. The lack of any one of the additives may cause defects in the coating or coating film. For example, a wetting and leveling agent can improve the wettability and leveling of the coating, and by reducing the surface tension of the coating and the interfacial tension between the coating and the substrate, the coating is easier to spread and level on the surface of the substrate. If a wetting and leveling agent is lacking, shrinkage holes or orange peel phenomena may occur in the coating film. Defoamers are used to eliminate bubbles and foams that may be generated during the preparation and use of the coating. If there is a lack of defoamers in the coating, bubbles may remain in the coating or coating film, resulting in poor dispersion, prickly heat on the coating film, and other problems; thickeners, as rheological additives, can increase the viscosity and consistency of the coating, and improve its fluidity and anti-sagging performance. If there is a lack of thickeners in the coating, the viscosity will be too low, which will cause precipitation and stratification during storage, as well as sagging and uneven gloss of the coating film. The synergistic effect of these three additives can not only significantly improve the uniformity and stability of the coating, but also enhance the smoothness and flatness of the coating film. By improving the construction performance and film quality of the coating, the construction cycle can be shortened, the number of reworks can be reduced, and production efficiency can be improved. In addition, they also help to reduce paint waste and construction costs.
[0044] In some embodiments, the acrylate functionality of the polyurethane acrylate is 6 to 8. The "acrylate functionality" here refers to the number of acrylate groups that can participate in chemical reactions in each polyurethane acrylate molecule. This value has a direct impact on the curing rate of the polyurethane acrylate material - a higher functionality means that more active groups can participate in the curing process, thereby accelerating the curing and improving the polymerization efficiency of the material. In addition, this also helps to enhance the mechanical strength and wear resistance of the final material. When the functionality of the acrylate is in a higher range of 6 to 8, it indicates that this type of material can form a highly cross-linked network structure during the polymerization reaction. This highly cross-linked feature gives the coating or material better mechanical strength, hardness and resistance to chemicals.
[0045] In some embodiments, each molecule of polyurethane acrylate contains 2 to 3 photoinitiator structural units. As the number of these photoinitiator structural units increases, the number of sites that can absorb ultraviolet rays and generate more photoactive free radicals also increases, thereby accelerating the process of photocuring. When the polyurethane acrylate molecule contains two different types of photoinitiator structural units as shown in Formula I and Formula II at the same time, since they each have different absorption wavelength ranges, their combined use can expand the absorption range of ultraviolet light of the entire system. In this way, not only can the radiation light source be used more efficiently, but the curing time of the material can also be further shortened.
[0046] In some embodiments, the polyurethane acrylate is an aliphatic compound. Such aliphatic polyurethane acrylate exhibits excellent light resistance and weather resistance and is not prone to yellowing because its main chain is composed of saturated alkanes or cycloalkanes. In addition, the aliphatic structure can also give the polyurethane acrylate cured film excellent flexibility, thereby enhancing the impact resistance and crack resistance of the coating.
[0047] In some embodiments, polyurethane acrylate has the following characteristics: acrylate functionality is between 6 and 8, each molecule contains 2 to 3 photoinitiator structural units, and adopts an aliphatic structure. The combination of these characteristics can enable the material to achieve more excellent comprehensive performance.
[0048] In some embodiments, the solid content of polyurethane acrylate is 35% to 45%. Solid content refers to the percentage of the remaining non-volatile matter (i.e., solid components) in the total mass of the coating after removing solvents, diluents, and other volatile components in the coating formula. A higher solid content means that the coating contains more effective solid components. For polyurethane acrylate, a high solid content indicates that it contains more polyurethane acrylate polymer components. For example, the solid content can be typical but non-limiting values such as 35%, 37%, 39%, 41%, 43%, 45%. When the solid content of polyurethane acrylate is in the higher range of 35% to 45%, it means that the proportion of non-volatile matter in the coating is higher, while the content of volatile components such as water is lower. At the same drying time and curing temperature, this solid content range helps the coating film reach a solid state faster and accelerates the light curing process. In addition, such a solid content level also enables the coating to form a thicker and denser coating film after drying, thereby giving the coating better properties such as wear resistance, adhesion, and flexibility.
[0049] In some embodiments, the viscosity of the polyurethane acrylate at 25°C is 50 cP to 500 cP. As an example, the viscosity at 25°C can be 50 cP, 100 cP, 150 cP, 200 cP, 250 cP, 300 cP, 350 cP, 400 cP, 450 cP, 500 cP, etc., which are typical but non-limiting values. The polyurethane acrylate within this viscosity range has good fluidity at room temperature, is neither too viscous nor too fluid, and is therefore easy to process and apply. In addition, this viscosity range also helps to improve the stability of the coating and reduce the occurrence of stratification and precipitation.
[0050] In some embodiments, the number average molecular weight of polyurethane acrylate is 5000 g / mol to 20000 g / mol. As an example, the number average molecular weight can be 5000 g / mol, 7000 g / mol, 9000 g / mol, 10000 g / mol, 12000 g / mol, 14000 g / mol, 16000 g / mol, 18000 g / mol, 20000 g / mol and other typical but non-limiting values. The number average molecular weight reflects the average length and complexity of the polyurethane acrylate molecular chain. When the number average molecular weight is within the above range, it means that the molecular chain of polyurethane acrylate is relatively long, which helps to form a more complex and stable network structure. It helps to improve the mechanical properties and chemical stability of the coating.
[0051] In some embodiments, the defoamer includes a polyether-modified polysiloxane copolymer and a defoaming siloxane solution. The former is a defoamer that combines the advantages of polysiloxane and polyether. By introducing a polyether segment, the hydrophilicity of polysiloxane is enhanced, so that it is better dispersed in water-based coatings, not easy to precipitate, and has excellent stability and anti-foaming performance. The latter is a defoamer based on the chemical structure of siloxane, which is easily soluble in water-based coatings, can quickly penetrate into the foaming system, and maintain good compatibility with other components in the system. Defoaming siloxane has a strong defoaming ability, which can not only quickly eliminate a large amount of foam, but also maintain a long anti-foaming effect. When these two types of defoamers are used in combination, they can complement each other to build a more comprehensive defoaming system. In practical applications, polyether-modified polysiloxane copolymers can quickly disperse into the foaming system by virtue of their hydrophilicity and self-emulsification, while defoaming siloxane solutions rely on their low surface tension characteristics to quickly spread on the foam film and destroy the stability of the foam. This synergistic effect significantly improves the speed and effect of defoaming. Due to the complementary and synergistic effects of the two in terms of performance, when used in combination, the required dosage can be reduced while ensuring the same defoaming effect, thereby reducing production costs and reducing environmental impact. As an example: polyether-modified polysiloxane copolymer defoamers include: BYK-028, BYK-019 and other products produced by German BYK Company; TEGO-902W and other products produced by German Evonik Company; defoaming siloxane solution defoamers include: BYK-022, BYK-024, BYK-025, BYK-092, BYK-093 and other products produced by German BYK Company.
[0052] In some embodiments, the polyether-modified polysiloxane copolymer includes BYK-028 and TEGO-902W; the defoaming siloxane solution includes BYK-024. Among them, the chemical composition of BYK-028 includes modified polysiloxane and polyether compounds, contains hydrophobic particles, and does not contain volatile organic compounds (VOC); TEGO-902W is a polyether siloxane copolymer emulsion containing fumed silica; and the chemical composition of BYK-024 includes a mixture of defoaming polysiloxane and hydrophobic particles in polyethylene glycol, which also does not contain VOC. These three defoamer products are all suitable for water-based systems. When used in combination, they can not only improve the overall dispersion effect and defoaming and degassing speed, but also improve production efficiency and further optimize the quality of the coating.
[0053] In some embodiments, the mass ratio of BYK-028 to TEGO-902W and BYK-024 is (15-25): (25-35): 50. As an example, the mass ratio of the three can be 15:35:50, 18:32:50, 20:30:50, 22:28:50, 25:25:50 and other typical but non-limiting values. When the mass ratio of the three defoamers is within the above range, the defoaming efficiency is higher, the defoaming effect is better, and the coating quality is higher.
[0054] In some embodiments, the wetting and leveling agent includes at least one of polyether-modified polydimethylsiloxane and acetylene glycol. Among them, the polyether-modified polydimethylsiloxane-type wetting and leveling agent has better storage stability and is not easily invalidated by hydrolysis. The acetylene glycol-type wetting and leveling agent is known for its excellent ability to reduce dynamic surface tension, which helps to improve the spray wettability of the coating and reduce the occurrence of shrinkage cavities. In addition, acetylene glycol also has certain defoaming properties, which can further reduce bubbles in the coating and reduce the risk of prickly heat in the coating. As an example, the polyether-modified polydimethylsiloxane-type wetting and leveling agent can be listed as: BYK-3455, BYK-349 and other products produced by German BYK; acetylene glycol-type wetting and leveling agents can be listed as: 104E and other products produced by American Air Chemicals.
[0055] In some embodiments, the thickener includes an associative polyurethane thickener. Associative polyurethane thickeners are generally composed of polyurethane prepolymers containing specific hydrophilic groups (such as carboxyl or hydroxyl groups) and longer hydrophobic segments. In aqueous systems, the hydrophobic segments of these thickeners tend to aggregate with each other to form so-called "association regions" or "association points", and this non-covalent interaction increases the viscosity of the system. Compared with other types of thickeners, when applied to the UV light-curing coating of this embodiment, the associative polyurethane thickener can not only adjust the viscosity of the coating, but also better disperse the other ingredients in the formula, optimize the leveling and anti-sagging properties of the coating, improve the storage stability of the coating, and obtain a better coating surface effect. As an example, associative polyurethane thickeners can be listed as thickener products with the brand names of PUR299 or PUR44 produced by Mingling Company of Germany.
[0056] In some embodiments, the Stormer viscosity of the UV light-curing coating at 25°C is 70KU to 90KU. Stormer viscosity is a method for measuring the viscosity of coatings and other similar substances, usually measured by a Stormer viscometer. Stormer viscometer is a rotational viscometer, and its working principle is to measure the resistance of the liquid to the rotating body at a fixed speed to determine the viscosity of the liquid. The unit of Stormer viscosity is often expressed in KU (Krebs unit), which is a logarithmic function specifically used to describe the viscosity of the coating, especially for brush-applied and roller-applied coatings. According to the Chinese national standard GB / T 9269-2009 "Stormer Viscometer Method for Determination of Coating Viscosity", a specific method for measuring the viscosity of coatings using a Stormer viscometer is specified. Stormer viscosity, as a physical quantity reflecting the viscosity of a fluid, describes the strength of the interaction between molecules inside the fluid. The interaction force between molecules in a fluid determines its flow properties. As an example, the Stormer viscosity of UV light-curing coatings at 25°C can be typical but non-limiting values such as 70KU, 75KU, 80KU, 85KU, 90KU, etc. When the Stormer viscosity of the coating is within this range, it indicates that it has good fluidity, is conducive to uniform application during construction, simplifies construction difficulty and saves time, and helps to form a smooth and uniform coating film, improving the appearance quality of the coating.
[0057] In a second aspect, an embodiment of the present application provides a method for preparing a UV light-curing coating, comprising the following steps: providing raw materials for the UV light-curing coating according to the first aspect; mixing polyurethane acrylate, a wetting and leveling agent, a defoaming agent, and a thickener to obtain a mixed slurry, and when the fineness of the solid particles in the mixed slurry is ≤30μm, adding water and a thickener to the mixed slurry, and adjusting the Stormer viscosity to 70KU~90KU at 25°C to obtain a UV light-curing coating.
[0058] "The fineness of solid particles in the mixed slurry" refers to the average particle size of solid particles in the mixed slurry, which is a key indicator for measuring the degree of dispersion of the slurry. The fineness directly affects the hiding power, glossiness and flatness of the coating. If the solid particles are too large, the hiding power and glossiness of the coating may decrease, and the surface of the coating may become rough and uneven. Therefore, during the preparation process, the fineness must first reach a certain standard, that is, the fineness must be less than or equal to 30μm, so that the coating has basic properties, and then water and thickeners are added to adjust the viscosity.
[0059] Thickeners improve the rheological properties of coatings by increasing the viscosity of the system, thereby controlling the leveling, anti-settling and construction performance of the coating. If thickeners are added before the fineness is not up to standard, large particles may not be further dispersed, thus affecting the quality of the coating. Adding thickeners after the fineness is qualified can ensure that all solid particles are fully dispersed, and adjusting the viscosity at this time will not interfere with the previous control of fineness.
[0060] The UV light-curing coating prepared by the preparation method provided in this embodiment has a smooth and beautiful surface, good glossiness and excellent visual effect.
[0061] In some embodiments, the steps of mixing polyurethane acrylate, wetting and leveling agent, defoamer, and thickener can be as follows: add polyurethane acrylate to a stirring container, add wetting and leveling agent, defoamer, and thickener in sequence under stirring, and disperse at a speed of 800 to 2000 rpm to make it fully uniform. Within this dispersion speed range, it is helpful to better disperse each component in the base material, improve the dispersion uniformity, and further refine the particle size (fineness) to make the particle distribution more uniform.
[0062] In some embodiments, after testing the fineness of the mixed slurry to be ≤30μm and detecting that there are no shrinkage cavities, water and thickener are added to adjust the Stormer viscosity to 70.0-90.0KU / 25°C. "Shrinkage cavities" are mainly manifested as irregular, bowl-shaped or crater-shaped small depressions on the surface of the coating, which usually form an annular edge around a drop or a small piece of impurities. The presence of shrinkage cavities will seriously affect the aesthetics, glossiness and pollution resistance of the coating, and thus affect the overall quality of the coating. Checking shrinkage cavities before adjusting the viscosity of the coating can timely discover and deal with potential shrinkage cavities problems, avoid discovering these problems after the viscosity is adjusted, and thus improve the stability of the coating quality.
[0063] In a third aspect, an embodiment of the present application provides an application of the UV light-curing coating as described in the first aspect or the UV light-curing coating prepared by the preparation method described in the second aspect in the field of environmentally friendly coatings.
[0064] Since no photoinitiator is added to the formula of UV light-curing coatings, the photoinitiator structural unit in the polyurethane acrylate oligomer is used to generate active free radicals under UV irradiation, which promotes the UV cross-linking and curing of the carbon-carbon double bonds on the oligomer. This design concept eliminates the addition of photoinitiators, so that the final coating film has the characteristics of low odor and low discoloration, which is very suitable for application in the field of environmentally friendly coatings, such as furniture coatings, wood coatings, building interior and exterior wall coatings, automotive coatings, packaging coatings, and electronic and electrical equipment coatings.
[0065] In a fourth aspect, the present application provides a method for using the UV light-curing coating as described in the first aspect or the UV light-curing coating prepared by the preparation method as described in the second aspect, comprising the following steps: applying the UV light-curing coating on a substrate by spraying and / or roller coating; wherein the coating amount by the spraying method is 100 g / m 2 ~150g / m 2 The coating amount of the roller coating method is 5g / m 2 ~20g / m 2 ; Dry the coated substrate at a drying temperature of 40℃~60℃ for 1h~24h; then use UV light curing with a light curing energy of 300mJ / cm 2 ~1200mJ / cm 2 .
[0066] As an example: the method of using UV light curing coating includes the following steps:
[0067] (1) Apply UV curing coating to the substrate by spraying or roller coating. The coating amount of spraying is 100g / m 2 Up to 150g / m 2 , while the coating amount of roller coating is 5g / m 2 Up to 20g / m 2 .
[0068] (2) The coated substrate is placed in a dry environment at 40° C. to 60° C. for 1 hour to 24 hours.
[0069] (3) The dried substrate is subjected to UV light curing treatment, and the light curing energy is set to 300 J / cm 2 Up to 1200mJ / cm 2 .
[0070] The following describes the invention in conjunction with specific embodiments.
[0071] Example 1
[0072] The embodiment of the present application provides a UV light-curing coating, which includes the following components in weight percentage, based on the total weight of the UV light-curing coating as 100%: 65% polyurethane acrylate; 0.5% wetting and leveling agent (BYK-349); 0.4% defoamer (BYK-024); 0.5% thickener (PUR299); and 33.6% deionized water. The polyurethane acrylate is a resin product with a brand name of RS979 produced by Ruishi Chemical Industry in Jiaxing, Zhejiang. The RS979 resin is an aliphatic polyurethane acrylate oligomer with 6 to 8 acrylate functionalities, which contains 1 to 2 photoinitiator structural units as shown in Formula I, and has a solid content of 38% to 42%. The wetting and leveling agent (BYK-349) is a product with a brand name of BYK-349 produced by BYK in Germany. The defoamer (BYK-024) is a product with a brand name of BYK-024 produced by BYK in Germany. The thickener (PUR299) is a product of brand PUR299 produced by Mingling Company of Germany.
[0073] The preparation method of the UV light-curing coating comprises the following steps:
[0074] S1: Add polyurethane acrylate RS979 into the dispersion tank, and add wetting and leveling agent BYK349, defoamer BYK024, and thickener PUR299 in sequence while stirring at a speed of 500 r / min (first add 50% of the thickener PUR299), stir evenly, and then disperse at a speed of 800 r / min for 30 minutes;
[0075] S2: When the mixed slurry of step S1 has a fineness of ≤30 um and has no shrinkage cavities, deionized water and the remaining thickener are added to adjust the Stormer viscosity to 70.0-90.0 KU / 25°C to obtain a UV light-curing coating.
[0076] Example 2
[0077] The difference between Example 2 and Example 1 is that the dosage of each component of the UV light-curing coating is different, specifically: self-initiating polyurethane acrylate (RS979) 70%; wetting and leveling agent (BYK-349) 0.5%; defoaming agent (BYK-024) 0.4%; thickener (PUR299) 0.4%; deionized water 28.7%.
[0078] Example 3
[0079] The difference between Example 3 and Example 1 is that the dosage of each component of the UV light-curing coating is different, specifically: self-initiating polyurethane acrylate (RS979) 75%; wetting and leveling agent (BYK-349) 0.5%; defoamer (BYK-024) 0.4%; thickener (PUR299) 0.4%; deionized water 23.7%.
[0080] Example 4
[0081] The difference between Example 4 and Example 1 is that the dosage of each component of the UV light-curing coating is different, specifically: self-initiating polyurethane acrylate (RS979) 85%; wetting and leveling agent (BYK-349) 0.5%; defoaming agent (BYK-024) 0.4%; thickener (PUR299) 0.3%; deionized water 13.8%.
[0082] Example 5
[0083] The difference between Example 5 and Example 3 is that the UV light curing coating includes two defoamers BYK-028 and BYK-024, and the dosage of each component is different, specifically: self-initiating polyurethane acrylate (RS979) 75%; wetting and leveling agent (BYK-349) 0.5%; defoamer (BYK-024) 0.2%; defoamer (BYK-028) 0.2%; thickener (PUR299) 0.4%; deionized water 23.7%. Defoamer BYK-028 is a BYK-028 product produced by German BYK Company.
[0084] Example 6
[0085] The difference between Example 6 and Example 3 is that the components of the UV light curing coating include three defoamers BYK-028, TEGO-902W and BYK-024, and the dosage of each component is different, specifically: 75% of self-initiating polyurethane acrylate (RS979); 0.5% of wetting and leveling agent (BYK-349); 0.2% of defoamer (BYK-024); 0.1% of defoamer (BYK-028), 0.1% of defoamer (TEGO-902W); 0.4% of thickener (PUR299); and 23.7% of deionized water. The defoamer TEGO-902W is a product of the brand TEGO-902W produced by Evonik of Germany.
[0086] Comparative Example 1
[0087] The difference between Comparative Example 1 and Example 1 is that the components of the UV light-curing coating do not include a wetting and leveling agent, and the dosage of each component is different, specifically: 65% of self-initiating polyurethane acrylate (RS979); 0.4% of defoamer (BYK-024); 0.5% of thickener (PUR299); and 34.1% of deionized water.
[0088] Comparative Example 2
[0089] The difference between Comparative Example 2 and Example 1 is that: the self-initiating polyurethane acrylate in the components of the UV light-curing coating has different feeding amounts of each component, specifically: 65% of polyurethane acrylate, the polyurethane acrylate is a resin product with the brand name UCECOAT 7230 produced by Allnex Resin, the resin has 6 acrylate functionalities and 40% solid content; 2% of photoinitiator (2-hydroxy-2-methyl-1-phenyl-1-propanone); 0.5% of wetting and leveling agent (BYK-349); 0.4% of defoamer (BYK-024); 0.5% of thickener (PUR299); and 32.1% of deionized water.
[0090] Performance Testing
[0091] In order to verify the progress of the present invention, the UV curing coatings obtained in Examples 1 to 6 and Comparative Examples 1 to 2 were applied. The application ratio was: UV curing coating: water mass ratio = 100:4, application method: air spraying, and the application process was shown in Table 1.
[0092] Table 1
[0093]
[0094]
[0095] The paint film after construction was tested, and the basic performance of the paint was tested according to the test items of varnish products in HG / T 5183-2017 "Water-based UV-curing Wood Coatings"; the board surface odor test method: evaluate through human sense of smell, and find 5 testers to smell the board surface to evaluate the odor; the board surface color change test method: evaluate through the color difference value before and after UV curing of the coating film. The test results are shown in Tables 2 and 3.
[0096] Table 2
[0097]
[0098] Table 3
[0099]
[0100]
[0101] As can be seen from Table 2 and Table 3, the coatings prepared by Example 1, Example 2, Example 3, Example 4, Example 5, Example 6, and Comparative Example 1, after UV curing, no obvious odor appeared on the board surface, and the color difference value of the color change of the board surface was also very small (usually, the UV coating with the addition of photoinitiator will have a color difference of more than 0.6 after UV curing). Among them, due to the addition of photoinitiator, the coating prepared by Comparative Example 2, after UV curing, the board surface has obvious odor, and the color difference value of the color change of the board surface is also very large. Among them, due to the lack of addition of substrate wetting agent in Comparative Example 1, the coating appearance has the disadvantages of shrinkage cavities and floweriness. Among them, due to the reasonable combination of defoamer system, the glossiness of the board surface of Example 5 and Example 6 is higher than that of Example 3. Based on the above experimental data and analysis, it can be concluded that the UV light-curing coating proposed in this application has a smaller board surface odor and a lower degree of discoloration, and other properties also meet the relevant standards.
[0102] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present application, rather than to limit them; although the present application has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein by equivalents; and these modifications or replacements do not make the essence of the corresponding technical solutions deviate from the scope of the technical solutions of the embodiments of the present application, and they should all be included in the scope of the claims and specification of the present application. In particular, as long as there is no structural conflict, the various technical features mentioned in the various embodiments can be combined in any way. The present application is not limited to the specific embodiments disclosed herein, but includes all technical solutions that fall within the scope of the claims.
Claims
1. A UV light curing coating, characterized in that: Taking the total weight of the UV light curing coating as 100%, the following components are included in weight percentage: Wherein, the polyurethane acrylate contains a photoinitiator structural unit, and the structural formula of the photoinitiator structural unit is shown in Formula I or Formula II: Wherein, * indicates the connection site.
2. The UV light curing coating according to claim 1, characterized in that: The polyurethane acrylate satisfies at least one of the following (1) to (5): (1) The acrylate functionality of the polyurethane acrylate is 6 to 8; (2) Each molecule of the polyurethane acrylate contains 2 to 3 photoinitiator structural units; (3) The solid content of the polyurethane acrylate is 35% to 45%; (4) The viscosity of the polyurethane acrylate at 25° C. is 50 cP to 500 cP; (5) The number average molecular weight of the polyurethane acrylate is 5000 g / mol to 20000 g / mol.
3. The UV light curing coating according to claim 1, characterized in that: The defoaming agent comprises a polyether-modified polysiloxane copolymer and a foam-breaking siloxane solution.
4. The UV light curing coating according to claim 3, characterized in that: The polyether-modified polysiloxane copolymer includes BYK-028 and TEGO-902W; and the foam-breaking siloxane solution includes BYK-024.
5. The UV light curing coating according to claim 4, characterized in that: The mass ratio of the BYK-028 to the TEGO-902W and the BYK-024 is (15-25):(25-35):
50.
6. The UV light curing coating according to any one of claims 1 to 5, characterized in that: The wetting and leveling agent includes at least one of polyether-modified polydimethylsiloxane and acetylene glycol; and / or, The thickener includes an associative polyurethane thickener.
7. The UV light curing coating according to any one of claims 1 to 5, characterized in that: The Stormer viscosity of the UV light-curing coating at 25° C. is 70 KU to 90 KU.
8. A method for preparing a UV light-curing coating, characterized in that: The following steps are involved: Providing raw materials for the UV light-curing coating according to any one of claims 1 to 7; The polyurethane acrylate, the wetting and leveling agent, the defoamer, and the thickener are mixed to obtain a mixed slurry. When the fineness of the solid particles in the mixed slurry is ≤30 μm, the water and the thickener are added to the mixed slurry, and the Stormer viscosity is adjusted to 70 KU to 90 KU at 25° C. to obtain the UV light-curing coating.
9. Use of the UV light-curing coating according to any one of claims 1 to 7 or the UV light-curing coating prepared by the preparation method according to claim 8 in the field of environmentally friendly coatings.
10. A method for using the UV light-curing coating according to any one of claims 1 to 7 or the UV light-curing coating prepared by the preparation method according to claim 8, characterized in that: The following steps are involved: The UV light curing coating is applied to the substrate by spraying and / or roller coating; wherein the coating amount by the spraying method is 100g / m 2 ~150g / m 2 The coating amount of the roller coating method is 5g / m 2 ~20g / m 2 ; Dry the coated substrate at a drying temperature of 40°C to 60°C for 1h to 24h; Then UV light curing was carried out with a light curing energy of 300 J / cm 2 ~1200mJ / cm 2 .
Citation Information
Patent Citations
Water-based UV plastic coating as well as preparation method and application thereof
CN110437729A
Low-odor UV (ultraviolet)-curable three-proofing paint composition
CN110698974A
UV-cured water-based anti-yellowing white wood lacquer and preparation method thereof
CN112143370A
Cited By
Real-wood water-based highlight coating and preparation method thereof, and preparation method of automobile real-wood interior trim part
CN120775440A
Real wood waterborne high gloss paint, preparation method thereof and preparation method of automobile real wood interior part
CN120775440B